RELIEF DAN STRUKTUR STUPA CANDI BOROBUDUR DITINJAU SECARA ARKEOASTRONOMI - Kharisma Nabila; Pratama Dharma Surya; Mahbubi Satria Agusti Wirawan; Resty Khairul Nisa; Djaliati Sri Nugrahani (Badan Riset dan Inovasi Nasional, 2022)
Relationship between components of the Borobudur Temple and relative position of the stars in the universe. Archeoastronomy is a multidisciplinary study of the understanding of astronomical objects in the sky based on cultural relics. This article aims to understand the relationship between Borobudur Temple and archeoastronomy aspects. This study uses an archeoastronomical approach by calculating astronomical data related to star clusters and constellations. Research methods are carried out offline and online through literature studies, observations, and data analysis. The results of this study show that the reliefs of Borobudur Temple based on the Sudhana story on the Gandavyuha reliefs have a relationship with the relative position of the stars in the universe. This is shown through the depiction of seven small spheres interpreted as the pleiades star cluster. Another component relationship, is therelationship between the 72 stupas of Borobudur Temple and the solstice and the use of the Pleiades star cluster by the ancient people of Borobudur as a marker of the seasonal system.